PENGARUH JOB DEMAND, JOB RESOURCE, JOB BURNOUT, DAN WORK ENGAGEMENT TERHADAP TURNOVER INTENTION PADA PT. BANK ABC KANTOR PUSAT - Rahmandika, Harris Prasetya (Fakultas Ekonomi Universitas Wisnuwardhana, 2025)
This study examines the effect of job demands and job resources on the level of physical and mental fatigue of employees, a sense of employee's positive emotional attachment to work, and employees' intention to leave their job with the research object of the AMK division (Accounting, Management, and Finance) at PT. Bank Rakyat Indonesia uses the SEM test. This study took 70 respondents who were employees with permanent status who worked in the division. Where the variable job demands was measured by 5 indicators, job resources was measured by 6 indicators, job burnout was measured by 15 indicators, work engagement was measured by 9 indicators, and turnover intention was measured by 6 indicators. Each indicator is measured on a 5-point Likert scale. The results of this study and supported by previous studies that discussed the same topic, found that job demands had a significant positive effect on job burnout, and a significant negative effect on work engagement. Then job resources have a significant negative effect on job burnout, and have a significant positive effect on work engagement. Then job burnout has a significant positive effect on turnover intention, and work engagement has a significant negative effect on turnover intention. Keywords: job burnout, job demands, job resources, turnover intention, work engagement